Deficits in functional trait diversity following recovery on coral reefs. Issue 1918 (8th January 2020) - McWilliam, Mike; Pratchett, Morgan S.; Hoogenboom, Mia O.; Hughes, Terry P.
Abstract : The disturbance regimes of ecosystems are changing, and prospects for continued recovery remain unclear. New assemblages with altered species composition may be deficient in key functional traits. Alternatively, important traits may be sustained by species that replace those in decline (response diversity). Here, we quantify the recovery and response diversity of coral assemblages using case studies of disturbance in three locations. Despite return trajectories of coral cover, the original assemblages with diverse functional attributes failed to recover at each location. Response diversity and the reassembly of trait space was limited, and varied according to biogeographic differences in the attributes of dominant, rapidly recovering species. The deficits in recovering assemblages identified here suggest that the return of coral cover cannot assure the reassembly of reef trait diversity, and that shortening intervals between disturbances can limit recovery among functionally important species.